The Effect of Financial Performance and Good Corporate Governance on Company Value - Watim Maysaroh; Partiwi Partiwi; Eko Budi Prasetyo (DIPONEGORO UNIVERSITY, 2024)
The aim of this research is to determine the effect of financial performance as proxied by return on equity and Good corporate governance as proxied by the GCG index on company value as measured by Tobin's Q. This research method uses a quantitative approach. The sampling technique uses purposive sampling with secondary data sources in the form of financial reports. The objects of this research are 26 companies listed on the Indonesian Stock Exchange. The research results show that financial performance as measured using ROE has no effect on company value. Meanwhile, GCG as measured using the GCG index has a significant positive effect on company value.